Excess cash, trading continuity, and liquidity risk - Huang, Winifred; Mazouz, Khelifa (Journal of Corporate Finance, 2018)
This study investigates the impact of excess cash on the liquidity risk faced by investors and their required liquidity premium. It shows that excess cash improves trading continuity and reduces both liquidity risk and the cost of equity capital. These findings are consistent with the view that firms with excess cash attract more traders even when market liquidity dries up. The increase in investors' trading propensity reduces stock price exposure to shocks to market liquidity and the liquidity premium required by investors. We also examine the impact of excess cash on firm value. We show that while the direct effect of excess cash on firm value is negative, its indirect effect through liquidity is significantly positive, indicating that investors are less likely to sanction (or even reward) illiquid firms for holding excess cash. Further analysis suggests that the liquidity benefits of excess cash are greater for financially constrained firms and firms with high growth opportunities. Our results are robust over time, after addressing endogeneity concerns, and to alternative estimation methods and alternative measures of liquidity.